Vaping Disparities at the Intersection of Gender Identity and Race/Ethnicity in a Population-Based Sample of Adolescents. Issue 3 (23rd July 2021) - Felner, Jennifer K; Andrzejewski, Jack; Strong, David; Kieu, Talia; Ravindran, Madhumitha; Corliss, Heather L
Abstract: Background: Transgender adolescents use vape products (eg, e-cigarettes) at higher rates than cisgender adolescents. Little is known about how these disparities differ from the intersectional perspective of both gender identity and race/ethnicity. Methods: We examined disparities in past 30-day vaping frequency at the intersection of gender identity and race/ethnicity among adolescents participating in two pooled waves of the population-based California Healthy Kids Survey ( N = 953 445; 2017–2019). Generalized linear mixed models included gender identity-by-race/ethnicity interactions and adjusted for potential confounders. Stratified models quantified relationships between gender identity and vaping within race/ethnicity strata and between race/ethnicity and vaping within gender identity strata. Results: Transgender adolescents of color were more likely to report a higher frequency of vaping than cisgender white adolescents. In models stratified by race/ethnicity, transgender adolescents evidenced greater odds of more frequent vaping than cisgender adolescents of the same race/ethnicity; disparities were greatest between transgender and cisgender Black adolescents (adjusted odds ratio [AOR]: 6.05, 95% CI: 4.76–7.68) and smallest between transgender and cisgender white adolescents (AOR: 1.20, 95% CI: 1.06–1.35). In models stratified by gender identity, disparities were greatest between transgender Black and transgender white adolescents (AOR: 2.85, 95% CI: 2.20–3.70) and smallest between transgender multiracial and transgender white adolescents (AOR: 1.28, 95% CI: 1.05–1.58). Similar, though less consistent, patterns emerged for adolescents of color unsure of their gender identity relative to cisgender white adolescents. Conclusion: Transgender adolescents of color may be especially vulnerable to vaping disparities. Future research should identify and intervene on causal mechanisms undergirding disparities. Implications: Research finds that transgender adolescents use vape products at higher rates than their cisgender peers, however, little is known about how patterns of adolescent vaping may differ by both gender identity and race/ethnicity, information needed to inform culturally tailored prevention and control initiatives to decrease adolescent vaping disparities. Our analysis of data from a population-based adolescent health survey finds evidence of magnified disparities in vaping frequency among transgender adolescents of color.